Neither vaginal nor buccal administration of 800 μg misoprostol alters mucosal and systemic immune activation or the cervicovaginal microbiome: a pilot study. (1st November 2016) - Kalams, Spyros A.; Rogers, Lisa M.; Smith, Rita M.; Barnett, Louise; Crumbo, Katie; Sumner, Shonda; Prashad, Naomi; Rybczyk, Kyle; Milne, Ginger; Dowd, Scot E.; Chong, Erica; Winikoff, Beverly; et al.
Abstract: Objectives: The aim of the study was to assess the extent to which misoprostol alters mucosal or systemic immune responses following either buccal or vaginal administration. Methods: This was a prospective, crossover pilot study of 15 healthy, reproductive-age women. Women first received 800 μg misoprostol either via buccal or vaginal administration and were crossed over 1 month later to receive the drug via the other route. Cervicovaginal lavage samples, cervical Cytobrush samples, cervicovaginal swabs, urine and blood were obtained immediately prior to drug administration and the following day. Parameters assessed included urine and cervicovaginal misoprostol levels, whole blood cytokine responses (by ELISA) to immune stimulation with lipopolysaccharide, peripheral blood and cervical lymphocyte phenotyping by flow cytometry, cervicovaginal antimicrobial peptide measurement by ELISA and vaginal microbial ecology assessment by 16S rRNA sequencing. Results: Neither buccal nor vaginal misoprostol significantly altered local or systemic immune and microbiological parameters. Conclusion: In this pilot study, we did not observe significant alteration of mucosal or systemic immunology or vaginal microbial ecology 1 day after drug administration following either the buccal or vaginal route.